1991
DOI: 10.1007/bf00036114
|View full text |Cite
|
Sign up to set email alerts
|

Plantlet multiplication from white pine (Pinus strobus L.) embryos in vitro: bud induction and rooting

Abstract: White pine embryos were grown on 4 different media with 6 different benzyladenine (BA) concentrations. Maximum adventitious shoot initiation and growth were obtained on a modified Lepoivre medium with 20/zM BA. Modified Schenk and Hildebrandt, Murashige and Skoog, and Gresshoff and Doy media were also tested. Shoot elongation was achieved on half-strength basal medium lacking growth regulators. Three rooting experiments involving indole-3-butyric acid (IBA), sucrose concentration, shoot orientation, IBA pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The most suitable explants for induction of somatic embryogenesis may differ for each species. Previous studies have shown that in Pinus, somatic embryos can efficiently be induced from immature embryos at the early cotyledon stage, while for Picea mariana, slighty older embryos at the cotyledon stage are more effective [5]. Based on morphological observation and physiological research the embryonic development of conifers is divided into four stages: embryogenesis suspensor mass (ESM), early suspensor proembryos (ESP), late suspensor proembryos (LSP) and cotyledon embryos [6].…”
Section: Introductionmentioning
confidence: 99%
“…The most suitable explants for induction of somatic embryogenesis may differ for each species. Previous studies have shown that in Pinus, somatic embryos can efficiently be induced from immature embryos at the early cotyledon stage, while for Picea mariana, slighty older embryos at the cotyledon stage are more effective [5]. Based on morphological observation and physiological research the embryonic development of conifers is divided into four stages: embryogenesis suspensor mass (ESM), early suspensor proembryos (ESP), late suspensor proembryos (LSP) and cotyledon embryos [6].…”
Section: Introductionmentioning
confidence: 99%
“…For conifer propagation, it is known that the most critical factors are kinds of explants, media components and cytokinin treatment [1,2]. To date, the best results have been obtained using mature zygotic embryos and embryonic explants, and BA alone or in combination with NAA has been shown very effective in promoting bud differentiation in most of the Pinus species [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Outros trabalhos como os de David et al (1982), Abdullah et al (1985), Bermudez & Sommer (1987) Bionde & Thorpe (1982) obtiveram estatisticamente melhores resultados com BAP na indução de gemas em cotilédones a 5x 10-5 M (11,265 mgll), mesmo resultado obtido por Schwarz et alo (1988). Comparando-se com o trabalho Chesick et al (1991) e Saravitz et alo (1991), nota-se que estas concentrações estão altas, em relação as usadas neste trabalho, ou seja 0,5 mgll e 1,0 mgll, para a parte superior dos embriões. Tabela 26 -Valores médios para NG de Pinus elliottU varo elliottii, mantidos em duas diferentes concentrações (2,5 e 5,0 mgll de BAP) nas fases de Ind.1 e Ind.2.…”
Section: Relação Dos Experimentos Realizadosunclassified